Fairy rings, associated fungi, and assessment of their distribution across environmental variables using GIS. (April 2021) - Miller, Steven L.; Gongloff, Abbie
Abstract: Fairy rings are conspicuous features of the Laramie Basin of southeastern Wyoming. Ten fairy ring sites chosen for intensive study were located using a small plane and 415 whole and partial fairy rings were georeferenced and ground-truthed. Fairy ring forming fungi were identified using a combination of taxonomy and ITS fungal barcode sequence comparisons. Precipitation, vegetation, soil type, elevation, slope, and slope aspect were queried using GIS. Eight fairy ring forming species were identified from the sites, including three unknown species, and two taxa not previously reported to form fairy rings. Most fairy rings occurred in drier mixed-grass prairie vegetation, whereas a small percentage occurred in mesic shrub dominated riparian vegetation. Most fungal species exhibited preferences for elevation and slope aspect, and rings were scarce on east facing slopes. The identity and autecology of individual fairy ring fungi and importance of environmental variables to fairy ring biology is discussed.